Policy Reforms and Agriculture Development in Central Asia - Djalalov, Sandjar.; Djalalov, Sandjar.; Babu, Suresh Chandra.; Babu, Suresh Chandra. (Natural Resource Management and Policy,, 2006)
The Central Asian republics – Kazakhstan, the Krygyz Republic, Tajikistan, Turkmenistan, and Uzbekistan – are transitioning from centrally planned economies to market-oriented systems. This volume addresses the process and policy reforms these countries face and how the reforms may impact agricultural development in a region that has experienced varying degrees of economic growth over the fifteen years since independence. It offers expert policy research and analysis and provides research-based information for generating policy recommendations that are relevant to each country as well as similar evidence from other transitional economies, including China, Vietnam, and selected Eastern European countries. Suresh Chandra Babu is a Senior Research Fellow and Program Leader at the International Food Research Policy Institute (IFRPI), in Washington, D.C. where he coordinates its research and outreach programs in Central Asia. He has trained more than 1,000 policy analysts and has consulted with international organizations such as the World Bank, the Asian Development Bank, and UNICEF. Dr. Babu received his Ph.D. in economics from Iowa State University in the United States. Sandjar Djalalov is a principal researcher at the Center for Efficient Economic Policy in Uzbekistan where he conducts research on production, marketing, investment, and consumption behavior of different types of farms in Uzbekistan and Central Asia. He is also a senior lecturer in the Tashkent Institute of Engineering for Irrigation and Agricultural Mechanization. Dr. Djalalov received his Ph.D. from the Institute of Macroeconomics and Social Investigation in Tashkent in Uzbekistan.